Effect of impurity ions on preparation of novel saponifier for rare earth extraction - 肖燕飞 冯宗玉 黄小卫 黄莉 徐旸 侯永可 王猛 (Journal of rare earths, 2013)
Magnesium bicarbonate, prepared by the carbonation of magnesium hydroxide slurry, was used as a novel saponifier to eliminate the ammonia nitrogen pollution in the rare earth extraction separation process. The effect of impurity ions introduced by system on the carbonation reaction of magnesium hydroxide was studied in the work. The results showed that the presence of Ca2＋could lead to side reactions so as to reduce the conversion rate of magnesium hydroxide, and a small number of rare earth ions would have great influence on the carbonation reaction. What’s more, there was no influence on carbonation reaction with the low concen-tration of Na＋or Mg2＋, the conversion rate of magnesium hydroxide could reach above 96%. This paper showed a practical theory which could provide scientific guidance for the preparation of novel saponifier in rare earth extraction separation process.